Penguatan Karakter Anti Korupsi bagi Siswa di SMA Mega Islamic Boaring School Kota Semarang - Eko Handoyo; Wasino Wasino; Tutik Wijayanti; Lailasari Ekaningsih; Aprilia Rizki Saputri; Siti Fatimah; Bagus Darmawan (Jurnal Masyarakat Mengabdi Nusantara, 2024)
Corruption is a crucial problem and an extraordinary crime that has wide-ranging impacts on society, the nation, and the state. The issue of corruption certainly requires serious attention. This cannot be separated from the fact that corruption has become commonplace, where its presence can be found from the central to regional levels, including rural areas. The cases of this crime continue to increase year by year. The rampant corruption cases necessitate eradication efforts involving every element of society by instilling anti-corruption values in daily life. This can be packaged through strengthening anti-corruption character as a strategic step by educating and reinforcing mental attitudes in a structured way to foster and strengthen anti-corruption behavior. The target for strengthening anti-corruption character is universal, regardless of age, gender, environment, or educational level. As long as a person can receive anti-corruption education, this step will be effective as a strategy to prevent and reduce corruption. Educational institutions are one of the bodies that need to implement anti-corruption education programs, as seen at Mega Islamic Boarding School High School in Semarang City. The eradication of corruption by instilling anti-corruption education is very important, especially for students, as they are the younger generation who will one day hold the future of the nation. Moreover, Mega Islamic Boarding School High School in Semarang City is an Islamic-based educational institution, which firmly holds that corruption is forbidden because it threatens human safety and causes harm to dignity and wealth, and those who commit it will face penalties not only in this world but also in the hereafter